Modern farm improvements - Walter, Merton Luther (My University, 1907)
Introduction: The subject of, “Modern Farm Improvements,” is so broad and comprehensive that no writer has, as yet, more than fairly entered upon the subject. The scope of this work shall of necessity be confined to a comparatively few of the salient points. The aim being to bring together some of the most up to date and satisfactory views and adaptations of modern methods and appliances to meet the needs of the farmer. Conditions and tastes differ so greatly that no set of rules can be laid down to govern the individual needs of all. There are many things however that demand practically the same treatment under all conditions. We shall therefore consider some of those things which have a general adaptation to all cases.
Citation: Walter, Merton Luther. Modern farm improvements. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Farm Improvements; Technological Advancement; Agricultural Tools; Improving Agriculture; Theses; Manuscripts (documents)